Dynamics and structural features of employment in the United States of America - N. E. Petrovskaya (Управление)
The purpose of the study is to identify trends and problems of employment in the United States. The main objectives of the article are defined in accordance with the stated goal: to study the dynamics of employment in the 21st century, to assess participation in the labor force by different age groups and socio-demographic characteristics, to consider the problems of youth employment, scientific and engineering personnel, to show the role of small business in providing employment, analyze gender and part-time employment issues in the US labor market. The paper uses the system, economic-statistical, logical, and comparative analysis approaches. The study is based on data from the Bureau of Labor Statistics of the U.S. Department of Labor. The relevance of the research topic is due to the fact that employment is an integral element of life that has a significant impact on both the socio-economic and political situation in the country and in the world. The analysis made it possible to identify current trends. Among the long-term challenges, there is a decline in the economic activity of the American population. The workforce is aging and transforming. Due to immigrants and the growth of the number of young racial-ethnic groups that identify themselves as multi-racial, there is a trend towards an increase in the multinationality of the United States. The most vulnerable groups of the population are youth, women, as well as people with a low level of education. The correlation between the level of education, unemployment and income is shown. One of the long-term trends is the growth of employment in sectors related to research, introduction of technological innovations and use of scientific and engineering knowledge.